2023
DOI: 10.3390/jcm12041615
|View full text |Cite
|
Sign up to set email alerts
|

Early Strokes Are Associated with More Global Cognitive Deficits in Adults with Sickle Cell Disease

Abstract: This study sought to link neurocognitive profiles in sickle cell disease (SCD) patients with clinical characteristics. We conducted a prospective cohort study of adults with SCD who underwent comprehensive neuropsychological assessment at the UMGGR clinic at Henri Mondor Hospital, Créteil (France). A cluster analysis was performed based on neuropsychological testing scores. The association between clusters and clinical profiles was assessed. Between 2017 and 2021, 79 patients with a mean age of 36 [range 19–65… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 44 publications
(48 reference statements)
0
5
0
Order By: Relevance
“…However, Couette et al. [ 17 ] showed that, although the occurrence of stroke episodes did not affect global cognition, the time of the first stroke did: SCD patients with childhood stroke seem to be at increased risk of a global cognitive deficit profile. Furthermore, MoCA scores mirrored the severity of the cognitive deficits.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Couette et al. [ 17 ] showed that, although the occurrence of stroke episodes did not affect global cognition, the time of the first stroke did: SCD patients with childhood stroke seem to be at increased risk of a global cognitive deficit profile. Furthermore, MoCA scores mirrored the severity of the cognitive deficits.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, MoCA scores mirrored the severity of the cognitive deficits. The paediatric group also had lower educational attainment, which could be explained in part by the disruption of the patient's schooling due to childhood strokes [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…FSIQ predicts attendance to appointments 46 and executive dysfunction correlates with workforce engagement, independence with tasks and socialization 51 . Some literature has suggested that early CVA and SCI are associated with more severe or more global cognitive deficits, even in the absence of radiological evidence of a specific area of ischemia 52 …”
Section: Neurocognitive Impairmentmentioning
confidence: 99%
“…51 Some literature has suggested that early CVA and SCI are associated with more severe or more global cognitive deficits, even in the absence of radiological evidence of a specific area of ischemia. 52 Cerebrovascular accidents (CVAs), silent cerebral infarction (SCI) and ageing are common primary causes of neurocognitive symptoms in SCD. 47,53 Severe anaemia, lower foetal haemoglobin levels, pathological electroencephalograms and abnormal transcranial Doppler velocities join CVAs in predicting deficits in attention, memory, executive function and sensory-motor skillset.…”
Section: N Eu Rocogn Iti V E I M Pa Ir M E N Tmentioning
confidence: 99%
“…Patients with sickle cell disease who have a history of childhood stroke are at an increased risk of global cognitive deficits. Despite the high prevalence of these cognitive disorders documented by several studies, there is no standardized approach to their screening and there is still, currently, a lack of data on rehabilitation for stroke and cognitive difficulties in people with sickle cell disease across the world, including even in high income countries ( 14 , 15 ).…”
Section: Current Situationmentioning
confidence: 99%